Semi-Analytical Solution for Functionally Graded Solid Circular and Annular Plates Resting on Elastic Foundations Subjected to Axisymmetric Transverse Loading (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, the static analysis of functionally graded (FG) circular platesresting on linear elastic foundation with various edge conditions is carried out byusing a semi-analytical approach. The governing differential equations are derivedbased on the three dimensional theory of elasticity and assuming that the mechanical properties of the material vary exponentially along the thickness direction andPoisson's ratio remains constant. The solution is obtained by employing the statespace method (SSM) to express exactly the plate behavior along the graded direction and the one dimensional differential quadrature method (DQM) to approximate the radial variations of the parameters. The effects of different parameters(e.g., material property gradient index, elastic foundation coefficients, the surfacesconditions (hard or soft surface of the plate on foundation), plate geometric parameters and edges condition) on the deformation and stress distributions of the FGcircular plates are investigated.